THE PHENOMENON OF WOMEN SCIENTISTS IN 21ST CENTURY SCIENCE (World Bulletin of Education and Learning, 2026)
In today's scientific development, the active participation of women scientists is not only a matter of gender equality, but also one of the important factors of scientific progress. The development of science in the current era is in many ways closely related to intellectual diversity, social inclusion and innovative approaches, and the role of women scientists in this process is increasingly increasing. This article analyzes the phenomenon of women scientists from a socio-philosophical and scientific point of view, highlights their contribution to the development of science, existing systemic problems and ways to overcome them.
Keywords: Women scientists, gender equality, development of science, scientific activity, innovation, academic environment, social factors, modern era, scientific policy, intellectual potential, inclusive development, scientific cooperation.